Rethinking liberal equality : from a "utopian" point of view - Levine, Andrew, 1944- (Cornell University Press, 1998)
For more than a quarter century, academic political philosophy has been dominated by strains of liberal theory shaped decisively by John Rawls's germinal investigations of distributive justice and political legitimacy. By intervening sympathetically but critically into several ongoing debates initiated by Rawls's work, Andrew Levine suggests the possibility of a supra-liberal egalitarian political philosophy that incorporates the insights of recent developments in liberal theory, while reinvigorating the political vision of the historical Left. In marked opposition to the consensus, Levine argues that the vision of ideal social and political arrangements which motivated generations of progressive thinkers and political actors is anything but utopian and in fact is indispensable for curing contemporary liberalism of its tendency to acquiesce in a status quo that is ultimately at odds with democratic, egalitarian, and even liberal values.